Direct Control of Stem Cell Behavior Using Biomaterials and Genetic Factors - Jeong-Kee Yoon; Mi-Lan Kang; Joo Hyun Park; Kyoung-Mi Lee; Young Min Shin; Jin Woo Lee; Hyun Ok Kim; Hak-Joon Sung (Stem Cells International)
Stem cells have recently emerged as an important candidate for cell therapy. However, some major limitations still exist such as a small quantity of cell supply, senescence, and insufficient differentiation efficiency. Therefore, there is an unmet need to control stem cell behavior for better clinical performance. Since native microenvironment factors including stem cell niche, genetic factors, and growth factors direct stem cell fate cooperatively, user-specified in vitro settings are required to understand the regulatory roles and effects of each factor, thereby applying the factors for improved cell therapy. Among others, various types of biomaterials and transfection method have been employed as key tools for development of the in vitro settings. This review focuses on the current strategies to improve stemness maintenance, direct differentiation, and reprogramming using biomaterials and genetic factors without any aids from additional biochemicals and growth factors.